ANALISIS DUA KONEKSI PELANGI PADA GRAF HASIL OPERASI PERKALIAN KARTESIAN GRAF KIPAS F_(1,3) DAN GRAF LINGKARAN C_n SERTA KAITANNYA DENGAN KETERAMPILAN BERPIKIR TINGKAT TINGGI - Wijayanti, Elsy; Dafik, Dafik; Oktavianingtyas, Ervin (Department of Mathematics Education , University of Jember, 2018)
Abstract. The rainbow connection of the graph of G = (V, E) if for each pair of points u and v in G there is a path with points u and v as the end points on each side obtaining different colors, the path is called the rainbow path. The rainbow-connected number graph G is the smallest positive integer such that G has a rainbow connection staining denoted rc(G). While the graph is said to be a rainbow 2-connected staining on G if for each pair of points u and v on the sides there are 2 different paths, with u and v being the end points of each side obtaining different colors and 2 passages can not intersect each other, denoted rc2 (G). Let G be the graph connected with so that , with d is degrees. Let G be a rainbow so that where κ is the number of paths of rainbow connecting every two distinct points in G. The results of this research are new theorem about the rainbow connection and 2-rainbow connected. Keywords : rainbow connection, 2-rainbow connected, rainbow path